LEARNING FROM EXPERIENCE THE DYNAMICS OF POLICY AND PRACTICE: A CRITICAL ASSESSMENT OF POLICY CAPACITY FOR INNOVATIVE GOVERNANCE THAT NURTURES SOCIO-POLITICAL TRANSFORMATIONS - Chrispen Ciome (CV. RADJA PUBLIKA, 2024)
Southern African countries increasingly recognize that long-term growth and productivity challenges are tightly related to the capacity to innovate and to introduce new products, processes, services, and organizational routines in policy practice. This research assessed policy capacity for innovative governance as practices that aim to satisfy socio-political transformations. It is based on original data collected through a comprehensive survey of 30 purposively selected senior policy managers working within the region as provincial and national policy managers. These officials were strategically situated to assess and reflect upon the capacity for innovative governance in their areas of jurisdiction. The findings appear to show that Southern African countries are affected by the government overload challenges, bureaucracy bashing, public skepticism about the role of government; deplorable state of support for public policy infrastructure, and others. The research thus concludes that innovative approaches are needed to satisfy socio-political transformations. The research recommends rethinking the economic, social, and environmental sustainability of current policy and practice models and implores countries to embrace a collective reflection on finding new sources of growth for supporting a transition towards stronger, cleaner, and fairer economies.